Studi identifikasi keragaman jenis, feeding habit dan food habit ikan demersal pada bagian hilir sungai yeh sungi, Tabanan, Bali. - I Gusti Ngurah Alit Parka Yudha; I Wayan Arya; Sang Ayu Made Putri Suryani (GEMA AGRO, 2018)
This study aims to determine the diversity of demersal fish and feeding habits and food habits of demersal fish found in the lower reaches of the Yeh Sungi River. This research was carried out in the lower reaches of the Yeh Sungi River, Tabanan, Bali. This research began on April 17, 2016 until May 1, 2016. The research method used is descriptive exploratory method, namely by conducting a series of sampling activities of demersal fish species to identify the diversity of species and behavior (feding habit) of each type of demersal fish, as well as the food habit of each type of demersal fish. The results of the research on the diversity of demersal fish that have been found in the lower reaches of the Yeh Sungi River are quite diverse, based on the results of the study which captured 14 types of demersal fish in the lower reaches of the Yeh Sungi River. Feeding habits of 14 species found in demersal fish have nocturnal properties, by identifying the physical characteristics of demersal fish, especially in the form of mouths and fins, knowing some types of demersal fish that have adhesive fins prove that the fish look for food by attaching (passively) to the substrate of river rocks and tend to eat moss and detritus and are omnivorous. Demersal fish that do not have adhesive fins tend to be carnivorous and omnivorous, often looking for food by grabbing their prey, especially on the sand substrate on the riverbed. According to the results of analysis of abdominal surgery from 14 types of demersal fish found, 10 body cut objects from macrozoobenthos animals or food habits both intact and destroyed which were then matched with macrozoobenthos data which had previously been found on the bottom substrate downstream of the River. Yeh Sungi, the body pieces are white worms, red worms, silk worms / Tubifek sp, subsequent snails, small shrimp, short snails, dragonfly larvae, insects, detritus and moss.